(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Prostate cancer (PC) is the second most common malignant disease in men worldwide and, in Brazil, the most common, excluding non-melanoma skin cancer. Objective: To analyze the epidemiological profile of patients with prostate adenocarcinoma in the Western Mesoregion of Rio Grande do Norte. Methods: A retrospective study analyzed 737 medical records of patients with prostate adenocarcinoma between 2010 and 2019, considering data such as city, residence, age, ethnicity, marital status, education, and profession. Data were processed in Excel® 2021, analyzed in IBM® SPSS® Statistics 29, and visualized in QGIS® 3.34.5. Results: A higher incidence of PC was observed between 2015 and 2018, especially in 2018 (18.6%; n = 137). Most patients lived in urban areas (78.6%; n = 579), were married (67.3%; n = 496), and had a mean age of 79 years; 71.2% (n = 525) were between 70 and 89 years old. More than half self-declared as white (50.5%; n = 372) and 5.2% (n = 38) declared themselves black, which diverges from the literature. Regarding education, 25.9% (n = 191) had incomplete primary education and 12.2% (n = 90) had no schooling. Professionally, retirees (33.2%; n = 245) and farmers (23.6%; n = 174) predominated. Conclusion: The study revealed a discrepancy in the ethnic profile of patients compared to the literature, in which there is a higher incidence of PC among black men. Further research is recommended to understand the quality of life and factors associated with the prevalence of white patients with prostate adenocarcinoma.